Pregnancy and Birth Outcomes - Wu, Wei (IntechOpen, 2018)
More than 10% of the global burden of disease is due to pregnancy complications and adverse birth outcomes. Despite recent advances in obstetric medicine, pregnancy complications and adverse birth outcomes are a growing public health concern and economic burden on the healthcare system. This book will focus on the pregnancy complications and birth outcomes, from the aspects of gestational age, environmental, genetic, epigenetic risk factors, and delivery room management.